AI for Language Learning: Friend or Foe? - Sujatna, Meita Lukitawati; Astarina, Atri Nadia; Heryono, Heri (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This is a study of the implementation of artificial intelligence (AI), especially in language learning and teaching, especially in the 2021 stages. AI has taken significant roles in learning activities that focus on student-centered learning, namely the customization of the learning speed, direct feedback, and assessment which have benefited their intended users. It has also addressed language learning-teaching challenges, including pronunciation, vocabulary, grammar, cultural differences, and motivation. However, some issues need to be addressed and regulated to ensure the safe and effective use: privacy and security of the user, technical expertise, bias, cultural sensitivity, a lack of human interaction, ethical considerations, and over-reliance on technology. Furthermore, the benefits and limitations have yet to be determined based on their dominance or balance: On one side, AI enables the learners to decide how they want to learn, while the instructors have a virtual assistant to construct curricula, materials, and assessments. On the other hand, its impact on the students in general in other learning aspects must also be considered. Therefore, it is essential to investigate further its effectiveness in how One approach is to integrate AI-based language learning tools with traditional language instruction, providing learners with a comprehensive and balanced language learning experience. For example, AI-based tools can provide learners targeted instruction and feedback on specific aspects of language use. In contrast, traditional language instruction can provide learners with opportunities for authentic language use and interaction with native speakers and peers (Lambelet & Chassot, 2019). Keywords: AI, Foreign Language Learning, Student-centered Learning